Melatonin decreases breast cancer metastasis by modulating Rho‐associated kinase protein‐1 expression. Issue 1 (20th October 2015) - Borin, Thaiz Ferraz; Arbab, Ali Syed; Gelaleti, Gabriela Bottaro; Ferreira, Lívia Carvalho; Moschetta, Marina Gobbe; Jardim‐Perassi, Bruna Victorasso; Iskander, ASM; Varma, Nadimpalli Ravi S.; Shankar, Adarsh; Coimbra, Verena Benedick; Fabri, Vanessa Alves; de Oliveira, Juliana Garcia; et al.
Abstract: The occurrence of metastasis, an important breast cancer prognostic factor, depends on cell migration/invasion mechanisms, which can be controlled by regulatory and effector molecules such as Rho‐associated kinase protein (ROCK‐1). Increased expression of this protein promotes tumor growth and metastasis, which can be restricted by ROCK‐1 inhibitors. Melatonin has shown oncostatic, antimetastatic, and anti‐angiogenic effects and can modulate ROCK‐1 expression. Metastatic and nonmetastatic breast cancer cell lines were treated with melatonin as well as with specific ROCK‐1 inhibitor (Y27632). Cell viability, cell migration/invasion, and ROCK‐1 gene expression and protein expression were determined in vitro. In vivo lung metastasis study was performed using female athymic nude mice treated with either melatonin or Y27832 for 2 and 5 wk. The metastases were evaluated by X‐ray computed tomography and single photon emission computed tomography (SPECT) and by immunohistochemistry for ROCK‐1 and cytokeratin proteins. Melatonin and Y27632 treatments reduced cell viability and invasion/migration of both cell lines and decreased ROCK‐1 gene expression in metastatic cells and protein expression in nonmetastatic cell line. The numbers of 'hot' spots (lung metastasis) identified by SPECT images were significantly lower in treated groups. ROCK‐1 protein expression also was decreased in metastatic foci of treated groups. Melatonin has shown to be effective in controlling metastatic breast cancer in vitro and in vivo, not only via inhibition of the proliferation of tumor cells but also through direct antagonism of metastatic mechanism of cells rendered by ROCK‐1 inhibition. When Y27632 was used, the effects were similar to those found with melatonin treatment.